(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: COVID-19 outbreak posed a serious threat to public health and greatly impacted the life of professionals and students. Hence, this study aimed to evaluate the knowledge related to COVID-19 during a lockdown in Punjab, Pakistan. Subjects and methods: This cross-sectional online study recruited 833 participants (males=417, females=416) from major cities (Lahore, Islamabad, Rawalpindi, Gujranwala, Bahawalpur, Faisalabad, and Sialkot) in Punjab, Pakistan, during the months of March and April 2020. A pre-designed questionnaire was shared, among professionals (including pharmacists, paramedical staff, lawyers, businessmen, teachers) and students (including medical undergraduate and postgraduate students, and non-medical students), containing 12 questions regarding their knowledge of COVID-19. Data were collected using convenient sampling technique. Chi-square test and logistic regression model were applied for analysis using Statistical Package for Social Sciences (SPSS) software. Results: The mean age of the participants was 23 years ranged from 15-68 years. Of the 833 participants, 365 (43.8%) were well aware, 405 (48.6%) were aware and only 63 (7.6%) were not aware of COVID-19. Most of the participants (69.4%) did not know about coronaviruses (Severe Acute Respiratory Syndrome Coronavirus and Middle East respiratory syndrome-related coronavirus) before this pandemic. Using logistic regression analysis, age above 24 years, being a student (vs. being a professional) and a prior knowledge about coronavirus resulted in having higher odds of knowledge about COVID-19 with a significant p-value (<0.05). Conclusion: This study identifies that the majority of the participants had necessary knowledge about transmission, preventive measures and basic hygiene about COVID-19. However, there is a need to improve knowledge among the younger population and professionals.